Inspire@Smart Project raises its curtains, instilling high motivation in students - MUHAMMAD ZUFLI, ZUHARI (UMPSA, 2023)
PEKAN, 25 September 2023 - A total of 35 facilitators, including students and alumni of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), have successfully organized the Inspire@Smart Project programme to instill a sense of motivation in selected students from ten schools in the Pekan district.